Measuring Quality and Outcomes in Sports Medicine. - Ruzbarsky, Joseph J.; Marom, Niv; Marx, Robert G. (Clinics in Sports Medicine, 2018)
Patient-reported outcome measures (PROMs) are objective metrics critical to evaluating outcomes throughout orthopedic surgery. New instruments continue to emerge, increasing the breadth of information required for those intending to use these measures for research or clinical care. Although earlier metrics were developed using the principles of classic test theory, newer instruments constructed using item response theory are amenable to computer-adaptive testing and may change the way these instruments are administered. This article aims to define the psychometric properties that are important to understand when using all PROMs and to review the most widely used instruments in sports medicine.